Analysis of Cash Waqf Management in Baitul Maal Hidayatullah - Wiwik Widya Rizki; Rimi Gusliana Mais (BPJP - STEI, 2020)
Abstract—This study aims to analyze the management of cash waqf in Baitul Maal Hidayatullah (BMH). What are the strategies and processes for collecting cash waqf that are carried out at BMH, how to manage cash waqf funds collected at BMH, and how the distribution of cash waqf is carried out at BMH. This research method uses qualitative methods. The data used in this study are primary and secondary data. Primary data were obtained from interviews, while secondary data were obtained from processed data in the form of documentation data at BMH, data from books, and data from literature studies. Data collection methods in this study were carried out by observation, interview, and documentation. Data management method is done by descriptive analysis. The results showed that the strategy of collecting cash waqf by BMH was known to be divided into two, namely before the formation of Baitul Waqf and after the formation of Baitul Waqf. Before the formation of Baitul Waqf the strategy used by BMH was by retailing strategies in the form of canvassing personally and in groups. After the formation of Baitul Waqf the strategy used by BMH through two forms, namely conducting cooperation (partnerships) with several parties and conducting socialization and education to the community. The collection process after the formation of Baitul Wakaf is carried out in 3 (three) ways, namely coming directly to the BMH office, through direct transfer to the Baitul Wakaf account, and through partners. The collection process prior to the formation of Baitul Wakaf is only by coming directly to the BMH office and transferring to the BMH account. The management of cash waqf funds is done through a productive and traditional approach. Waqf funds that have been collected are channeled to several fields such as SME development, plantation, agriculture and animal husbandry, health, education, and social services.